Identification and Signature Sequences of Bacterial Δ4,5Hexuronate-2-O-Sulfatases - Wang, Shumin; Guan, Jingwen; Zhang, Qingdong; Chen, Xiangxue; Li, Fuchuan (Frontiers in Microbiology, 2019)
Glycosaminoglycan (GAG) sulfatases, which catalyze the hydrolysis of sulfate esters from GAGs, belong to a large and conserved sulfatase family. Bacterial GAG sulfatases are essential in the process of sulfur cycling and are useful for the structural analysis of GAGs. Only a few GAG-specific sulfatases have been studied in detail and reported to date. Herein, the GAG-degrading Photobacterium sp. FC615 was isolated from marine sediment, and a novel Δ4,5hexuronate-2-O-sulfatase (PB2SF) was identified from this bacterium. PB2SF specifically removed 2-O-sulfate from the unsaturated hexuronate residue located at the nonreducing end of GAG oligosaccharides produced by GAG lyases. A structural model of PB2SF was constructed through a homology-modeling method. Six conserved amino acids around the active site were chosen for further analysis using site-directed mutagenesis. N113A, K141A, K141H, H143A, H143K, H205A and H205K mutants exhibited only feeble activity, while the H310A, H310K and D52A mutants were totally inactive, indicating that these conserved residues, particularly Asp52 and His310, were essential in the catalytic mechanism. Furthermore, bioinformatic analysis revealed that GAG sulfatases with specific degradative properties clustered together in the neighbor-joining phylogenetic tree. Based on this finding, sixty Δ4,5hexuronate-2-O-sulfatases were predicted in the NCBI protein database, and one with relatively low identity to PB2SF was characterized to confirm our prediction. Moreover, the signature sequences of bacterial Δ4,5hexuronate-2-O-sulfatases were identified. With the reported signature motifs, the sulfatase sequence of the Δ4,5hexuronate-2-O-sulfatase family could be simply identified before cloning. Taken together, the results of this study should aid in the identification and further application of novel GAG sulfatases.